Birth prevalence of congenital talipes equinovarus in low‐ and middle‐income countries: a systematic review and meta‐analysis. Issue 3 (22nd January 2017) - Smythe, Tracey; Kuper, Hannah; Macleod, David; Foster, Allen; Lavy, Christopher
Abstract: Objective: Congenital talipes equinovarus (CTEV), or clubfoot, is a structural malformation that develops early in gestation. Birth prevalence of clubfoot is reported to vary both between and within low‐ and middle‐income countries (LMICs), and this information is needed to plan treatment services. This systematic review aimed to understand the birth prevalence of clubfoot in LMIC settings. Methods: Six databases were searched for studies that reported birth prevalence of clubfoot in LMICs. Results were screened and assessed for eligibility using pre‐defined criteria. Data on birth prevalence were extracted and weighted pooled estimates were calculated for different regions. Wilcoxon rank‐sum test was used to examine changes in birth prevalence over time. Included studies were appraised for their methodological quality, and a narrative synthesis of findings was conducted. Results: Forty‐eight studies provided data from 13 962 989 children in 20 countries over 55 years (1960–2015). The pooled estimate for clubfoot birth prevalence in LMICs within the Africa region is 1.11 (0.96, 1.26); in the Americas 1.74 (1.69, 1.80); in South‐East Asia (excluding India) 1.21 (0.73, 1.68); in India 1.19 (0.96, 1.42); in Turkey (Europe region) 2.03 (1.54, 2.53); in Eastern Mediterranean region 1.19 (0.98, 1.40); in West Pacific (excluding China) 0.94 (0.64, 1.24); and in China 0.51 (0.50, 0.53). Conclusion: Birth prevalence of clubfoot varies between 0.51 and 2.03/1000 live births in LMICs. A standardised approach to the study of the epidemiology of clubfoot is required to better understand the variations of clubfoot birth prevalence and identify possible risk factors.